Augmented reality‐based feedback for technician‐in‐the‐loop C‐arm repositioning. Issue 5 (1st October 2018) - Unberath, Mathias; Fotouhi, Javad; Hajek, Jonas; Maier, Andreas; Osgood, Greg; Taylor, Russell; Armand, Mehran; Navab, Nassir
Abstract : Interventional C‐arm imaging is crucial to percutaneous orthopedic procedures as it enables the surgeon to monitor the progress of surgery on the anatomy level. Minimally invasive interventions require repeated acquisition of X‐ray images from different anatomical views to verify tool placement. Achieving and reproducing these views often comes at the cost of increased surgical time and radiation. We propose a marker‐free 'technician‐in‐the‐loop' Augmented Reality (AR) solution for C‐arm repositioning. The X‐ray technician operating the C‐arm interventionally is equipped with a head‐mounted display system capable of recording desired C‐arm poses in 3D via an integrated infrared sensor. For C‐arm repositioning to a target view, the recorded pose is restored as a virtual object and visualized in an AR environment, serving as a perceptual reference for the technician. Our proof‐of‐principle findings from a simulated trauma surgery indicate that the proposed system can decrease the 2.76 X‐ray images required for re‐aligning the scanner with an intra‐operatively recorded C‐arm view down to zero, suggesting substantial reductions of radiation dose. The proposed AR solution is a first step towards facilitating communication between the surgeon and the surgical staff, improving the quality of surgical image acquisition, and enabling context‐aware guidance for surgery rooms of the future.